The Theory of Dyadic Morality and Moral Identity Explain the Public's Response to Harm Done by Government and Organisations - Bagozzi, Richard P.; Xie, Chunyan; Mari, Silvia; Oklevik, Ove (Journal of community & applied social psychology, 2024)
ABSTRACT Harm functions complexly in moral judgement but has been treated differently in the Social Intuitionist Model (SIM) and the Theory of Dyadic Morality (TDM). Both the SIM and TDM see felt harm as an outcome of experienced negative moral emotions (e.g., disgust), but the SIM regards harm as a kind of epiphenomenon in the sense that it does not affect moral judgement or behaviour, whereas the TDM interprets harm as an essential mediator of the link between negative moral emotions and immorality. The TDM also develops an explanation for how harm functions to initiate reactions to triggering events marked by an intentional agent causing injury to a vulnerable social actor. Here norms serve a regulatory function modulating the effects of harm committed by the agent on negative moral emotions. We conduct two experiments on representative samples of adults (N1=180;N2=192$$ N_1=180;N_2=192 $$) and address two different moral contexts (companies doing badly and government doing badly with respect to a threatened health crisis), two different normative moderators (moral identity and belief in conspiracies) and two different moral action tendencies (intentions and word of mouth). Harm is found to have direct and contingent mediated effects on moral action tendencies, in accord with the TDM. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement.